2008
DOI: 10.5424/sjar/200806s1-386
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant activity and effects of terpenoids on detoxication enzymes of the beet armyworm, Spodoptera exigua (Hübner)

Abstract: It has been determined the antifeedant activity of a mixture of limonoids 1,7-di-O-acetylhavanensin and 3,7-di-Oacetylhavanensin (F18), isolated from seeds of Trichilia havanensis Jacq. (Meliaceae), and the neo-clerodane diterpene scutecyprol A, isolated from Scutellaria valdiviana (Clos) Epling (Labiatae), on fifth instar larvae of the beet armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae). Choice and no-choice feeding assays, nutritional tests, and post-treatment studies indicated that scutecypro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
(27 reference statements)
5
18
0
Order By: Relevance
“…Based on the highest toxicity of thymyl cinnamate, the detoxification results showed that thymyl cinnamate affected the increasing of CE activity, whereas no significant increase was obtained in GST activity. Similar results were reported by Kumrungsee and Caballero, who found that both GST and CE activities were significantly increased in thymol‐treated larvae, and the GST activity was not significantly increased by the treatment of limonoid mixtures at a concentration below 1000 ppm, respectively. The increase in carboxylesterase activity may have been due to the uptake of the active compound by the insect, which progressively increased the amount of active components in the insect's body or a general induction of detoxification genes in response to secondary metabolites in the early stage of exposure .…”
Section: Discussionsupporting
confidence: 89%
“…Based on the highest toxicity of thymyl cinnamate, the detoxification results showed that thymyl cinnamate affected the increasing of CE activity, whereas no significant increase was obtained in GST activity. Similar results were reported by Kumrungsee and Caballero, who found that both GST and CE activities were significantly increased in thymol‐treated larvae, and the GST activity was not significantly increased by the treatment of limonoid mixtures at a concentration below 1000 ppm, respectively. The increase in carboxylesterase activity may have been due to the uptake of the active compound by the insect, which progressively increased the amount of active components in the insect's body or a general induction of detoxification genes in response to secondary metabolites in the early stage of exposure .…”
Section: Discussionsupporting
confidence: 89%
“…(Viana et al, 2007), Guarea trichilioides L., Guarea guidonia (L.) Sleumer, Melia azedarach L. (Rodríguez and Vendramim, 1997;De Brito et al, 2004), Trichilia havannensis (Jacq.) (Caballero et al, 2008), and Trichilia pallida Swartz (Roel and Vendramim, 1999;Roel et al, 2000;Roel and Vendramim, 2006). However, in the last few years, there have been studies with plants of other plant families, such as Quassia amara L. (Simaroubaceae) (Mancebo et al, 2000;Souza et al, 2007), Annona cherimola Mill.…”
Section: Introductionmentioning
confidence: 99%
“…GST and CYP450 activities decreased after leaf extract treatments. Although activities of some CYP450s are upregulated after exposure to plant allelochemicals (Caballero, López‐Olguín, Ruiz, Ortego, & Castañera, ), we interpret our data to show the leaf extracts exert differing influences on mosquito biochemical defense mechanisms.…”
Section: Discussionmentioning
confidence: 67%